c-rel regulates Ezh2 expression in activated lymphocytes and malignant lymphoid cells - Lim, Jun Feng (2015)
The polycomb group protein Ezh2 is a histone methyltransferase that modifies chromatin structure to alter gene expression during embryonic development, lymphocyte activation, and tumorigenesis. The mechanism by which Ezh2 expression is regulated is not well defined. In the current study, we report that c-Rel is a critical activator of Ezh2 transcription in lymphoid cells. In activated primary murine B and T cells, plus human leukemia and multiple myeloma cell lines, recruitment of c-Rel to the first intron of the Ezh2 locus promoted Ezh2 mRNA expression. This up-regulation was abolished in activated c-Rel-deficient lymphocytes and by c-Rel knockdown in Jurkat T cells. Treatment of malignant cells with the c-Rel inhibitor pentoxifylline not only reduced c-Rel nuclear translocation and Ezh2 expression, but also enhanced their sensitivity to the Ezh2-specific drug, GSK126 through increased growth inhibition and cell death. In summary, our demonstration that c-Rel regulates Ezh2 expression in lymphocytes and malignant lymphoid cells reveals a novel transcriptional network in transformed lymphoid cells expressing high levels of Ezh2 that provides a molecular justification for combinatorial drug therapy.